Self-Supported Smart Bacterial Nanocellulose–Phosphotungstic Acid Nanocomposites for Photochromic Applications - Santos, Moliria V.; Barud, Hernane S.; Alencar, Monica A. S.; Nalin, Marcelo; Toma, Sérgio H.; Araki, Koiti; Benedetti, Assis V.; Maciel, Indhira O.; Fragneaud, Benjamin; Legnani, Cristiano; Molina, Celso; Cremona, Marco; et al. (Frontiers in Materials, 2021)
Bacterial nanocellulose (BNC) is a natural biopolymer obtained by gram-negative bacteria’s using bacteria by means of a green and inexhaustible biotechnological process using glucose as producing source. BCN hydrogels is formed by cellulose nanofibrils that maintain an open network structure, an ideal matrix to produce new class of organic-inorganic nanocomposites (OIN) for multifunctional applications. he polyoxometalates (POMs) are complex molecules with several metallic ions sharing oxide ions, forming a highly symmetrical metal oxide cluster. Phosphotungstic acid (PWA), H3PW12O40 photoreduction process can be activated under ultraviolet irradiation, promoting color change. In this work, photochromic organic-inorganic nanocomposites were prepared by soaking phosphotungstic acid (H3PW12O40) in wet BNC membranes mats at room temperature. Semi-transparent and free-standing BNC/PWA nanocomposite with paper-like aspect were obtained. BNC network was able to control, stabilize and disperse PWA particles in a narrow nanometric distribution, and FTIR spectra indicated that the primary Keggin structure was also preserved in the nanocomposites, independently of the PWA content. BNC/PWA nanocomposites showed reversible photochromic behavior characteristic of the equilibrium between different tungsten oxidation states. PWA reduction (W6+→ W5+) and organic matrix oxidation is proposed to occur through a radical process involving the interaction of an electron from the oxygen atom of the PWA and hydrogen from BNC matrix. The photo-electrochemical behavior was studied by spectroelectrochemistry measurements. It is worth noting that all processes were still reversible in the timescale of the experiment and color changes could be observed in several cycles.